2014
DOI: 10.1177/0733464814533819
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Factors Associated With Walking and Physical Activity in Community-Dwelling Older Latino Adults

Abstract: BACKGROUND Ethnic/racial minorities often live in neighborhoods that are not conducive to physical activity (PA) participation. We examined perceived factors related to walking/PA among Spanish- and English-speaking older Latinos in a low-income, multi-ethnic neighborhood. METHODS Exploratory focus group study with Latinos stratified by preferred language and gender: English speaking women (n=7, M age=74.6); English speaking men (n=3, M age=69.3); Spanish speaking women (n=5, M age=66.4); Spanish speaking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…The 36 studies included in this review were published between 1998 and 2015. Twelve were undertaken in the USA [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], six in Canada [ 13 , 33 , 34 , 35 , 36 , 37 ], two in the UK [ 38 , 39 ], eight in Australia [ 12 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], two in New-Zealand [ 47 , 48 ], and one each in Ireland [ 49 ], Brazil [ 50 ], Sweden [ 51 ], Belgium [ 52 ] and Iceland [ 53 ], with one study having recruited from both Canada and the USA [ 54 ] ( Appendix A ). Sample sizes varied from eight to 396 participants with four studies not specifying a sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The 36 studies included in this review were published between 1998 and 2015. Twelve were undertaken in the USA [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], six in Canada [ 13 , 33 , 34 , 35 , 36 , 37 ], two in the UK [ 38 , 39 ], eight in Australia [ 12 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], two in New-Zealand [ 47 , 48 ], and one each in Ireland [ 49 ], Brazil [ 50 ], Sweden [ 51 ], Belgium [ 52 ] and Iceland [ 53 ], with one study having recruited from both Canada and the USA [ 54 ] ( Appendix A ). Sample sizes varied from eight to 396 participants with four studies not specifying a sample size.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in one recent qualitative study of older adults, Clancy, Balteskard, Perander, and Mahler (2015) concluded that in the experience of falls and falling, “participants’ stories reveals life courage and endurance and is more about getting up, staying up, and moving on than falling down.” (p. 9). Several studies have reported that older adults perceived adverse weather including ice, cold, snow as well as extreme heat as barriers to participating in physical activity (Chrisman et al, 2015; Marquez et al, 2014; Witcher et al, 2007). Also related to weather in rural communities, Chrisman et al (2015) found that loose gravel and muddy roads inhibited physical activity among adults in the rural Midwest USA.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, participants indicated the importance of the social benefits of exercise and suggested that easy access to programming-either through programs offered where people live, or by providing transportation to activities and classes-would help facilitate increased PA participation (Belza et al, 2004;Mathews et al, 2010). In these and other studies (Chan & Ryan, 2009;Clemes, Hamilton, & Griffiths, 2011;Guerin, et al, 2008;Kimura, Kobayashi, Nakayama, & Kakihana, 2015;Marquez et al, 2014), researchers have found that barriers to PA participation included personal (health/safety concerns) and environmental (lack of access and poor weather) factors.…”
Section: Introductionmentioning
confidence: 84%